3-T MRI in Patients who Received Anterior Cervical Discectomy and Fusion Surgery with MAVRIC SL IR Sequence: A Feasibility Study - Yang, Renjie; Liu, Changsheng; Li, Liang; Chen, Liang; Liu, Weiyin V.; Zha, Yunfei (Combinatorial Chemistry & High Throughput Screening, 2022)
Objective: We aimed to investigate the feasibility of multi-acquisition with variable resonance image combination slab selectivity inversion recovery (MAVRIC SL IR) sequence on 3.0 T MRI in patients with anterior cervical discectomy and fusion (ACDF) surgery compared to bandwidth-optimized short tau inversion recovery (STIR) sequence. Methods: Paired sagittal MR images of MAVRIC SL IR and bandwidth-optimized STIR sequences were acquired and analyzed for 21 patients after ACDF surgery with PEEK cage-plate construct. Quantitative comparisons were made on the metal artifact areas of paired mid-sagittal images. In qualitative analysis, the consistency of fat suppression and visibility of anatomic structures (bonemetal interface, surrounding soft tissues, and spinal cord) were independently assessed, based on a five-point scale by two musculoskeletal radiologists, who were blind to the images and patient details. Results: The application of the MAVRIC SL IR sequence resulted in a significant reduction of 48% in the mean area of metal artifacts (t = -7.141, p < 0.001). Based on the comments received from both the reviewers, the MAVRIC SL IR sequence showed greater visibility of the bone-metal interface (p < 0.001), considerable visibility of the surrounding soft tissues (p > 0.05) but worse visibility of the spinal cord (p < 0.001), including the consistency of fat suppression (p < 0.001) relative to the bandwidth-optimized STIR sequence. Conclusion: With significantly reduced metal artifacts, the MAVRIC SL IR sequence can be implemented in patients undergoing ACDF surgery with PEEK cage-plate construct for 3.0 T MRI, despite the poor visibility of the spinal cord.
Keywords: Magnetic resonance imaging